2021
DOI: 10.22159/ijap.2021v13i2.40094
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Nanospray With Self-Nanoemulsifying Drug Delivery System Using Sinergistic Combination of Melastoma Malabathricum L. Fraction and Gentamicin

Abstract: Objective: This study aimed to design a formula using Design-Expert software to obtain optimal Self-Nanoemulsifying Drug Delivery System (SNEDDS) formulas and to analyze nanospray characteristics of optimal SNEDDS. Methods: The study began with preparing ethanol extract from Melastoma malabathricum. The extract was then fractionated using ethyl acetate. The formulation design stage began with a solubility test of Melastoma malabathricum fraction and gentamicin (MFG) in various surfactants, co-surfactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
7
0
3
Order By: Relevance
“…Ciprofloxacin showed an MBC value of 65% against E. coli , S. aureus , and B. cereus . Previous studies had shown MBC values of 25 μg/mL, 10-25 μg/mL [ 10 ], and 1.83 μg/mL [ 14 ] against S. aureus , E. coli , and B. cereus . The leaf fraction of M. malabathricum inhibited the growth of S. aureus and B. cereus at a concentration of 35% and of E. coli at a concentration of 55%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciprofloxacin showed an MBC value of 65% against E. coli , S. aureus , and B. cereus . Previous studies had shown MBC values of 25 μg/mL, 10-25 μg/mL [ 10 ], and 1.83 μg/mL [ 14 ] against S. aureus , E. coli , and B. cereus . The leaf fraction of M. malabathricum inhibited the growth of S. aureus and B. cereus at a concentration of 35% and of E. coli at a concentration of 55%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown the efficacy of the leaf fraction of M. malabathricum in treating wounds. An ointment formulation of an ethanolic extract of M. malabathricum leaf, effective at 5% concentration [9], was applied to mice with injuries, leading to healing without any infection [10].…”
Section: Introductionmentioning
confidence: 99%
“…The polymer (X1 Eudragit RS100) and plasticizer (X2 sorbitol) concentrations were chosen as independent variables based on the existing related work. In contrast, (Y1) viscosity and (Y2) DT% as dependent variables were selected and VCZ was a constant value [15,16]. A statistical model is concerned with compositional response (degradation) Equation ( 1).…”
Section: Design Of Experiments (Doe) To Optimize the Formulationmentioning
confidence: 99%
“…The results of the stability study of the optimized VCZ in situ polymeric film formulation (F-5) after one month, two months, and six months at different storage conditions (in the refrigerator (4±2 ᵒC), room temperature (25±2 ᵒC/60±5% RH) and humidity control chamber (45±2 ᵒC/75±5% RH)) are shown in table 16. No noticeable/significant change in the drying time, transparency, stickiness, viscosity, the volume of solution delivered by actuation, density, spray angle, spray pattern, folding endurance, thickness, tensile strength, elongation at break, pH study, and Cumulative Drug Release (CDR) % of the optimized formulation was perceived during the study period; indicating exhibit of good stability by optimized VCZ in situ polymeric film formulation during the study period.…”
Section: Stability Studiesmentioning
confidence: 99%
“…Campuran dikondisikan dalam penangas air pada suhu 40°C selama 10 menit. Proses homogenisasi fraksi dalam carrier dimaksimalkan dengan vortex 1000 rpm selama 15 menit (14). Preparasi SNEDDS kombinasi fraksi etil asetat daun cengkodok Melastoma malabathricum L. dengan Gentamisin SNEDDS dibuat dengan kombinasi Tween 80: Propilenglikol:…”
Section: Metode Preparasi Snedds Kombinasi Fraksi Etil Asetat Daun Ce...unclassified